An Analysis of the Main Character Conflict of the Roommate Movie Script by Sonny Malhi - Mukhlas, Mukhlas; Asyari, Ahmad Khasan; Hidayah, Nurul; Kirom, Siti Masirotul; Pratama, Risky (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
This study provides a comprehensive examination of the primary character conflict in the movie script "Roommate" written by Sonny Malhi. The research examines the character of Rebecca, analyzing and classifying the internal and external difficulties she faces. This analysis provides vital insights into the development of her character, the psychological dynamics at play, and the narrative storytelling of the text. The findings highlight the importance of character analysis in literature and movies, emphasizing the intricacies of character motivations and interpersonal connections. Moreover, the study emphasizes the educational significance of utilizing film as a medium for learning, namely in the realm of language instruction and the examination of characters. By integrating audio-visual elements into instructional environments, educators can augment students' language proficiency, cultural consciousness, and analytical reasoning capabilities. Furthermore, the research highlights the significance of comprehending conflicts in literature and film within a multicultural framework. It aims to foster empathy, facilitate open discourse, and promote cultural understanding in various educational settings. Overall, the findings enhance the broader discussion on character analysis, conflict kinds, educational consequences, and intercultural relevance in the field of English teaching and learning, offering significant insights for both educators and researchers.Keywords: Movie, Script, Character Conflict, Roommate